Aromatherapy Effect of Lavander Essence and Mefenamic Acid on Dysmenorrhea: A Clinical Trial - Marzieh Davari; Shamila Mosharraf (Golestan University of Medical Sciences, 2014)
Background and Objective: Primary dysmenorrhea (PD) is one of the most prevalent gynecological disorders that about 50-70% of childbearing women experience it. To relieve this pain, we can use different methods such as chemical drugs that may have some side effects. Thus, we aimed to determine the aromatherapy effect of lavender extract on dysmenorrhea. Material and Methods: This double-blind clinical trial was conducted on 90 female students, aged 18 to 26, who suffered from PD. They were divided into two groups of case, received lavender essence and Mefenamic acid, and a control group received placebo. Participants were evaluated for the severity and duration of the menstrual pain during the three first-days of the beginning of bleeding before and after receiving drugs. For data analysis, we used descriptive statistics and inferential statistics, using spss software version 11. Results: Based on the findings, there is significant difference in pain severity and duration in lavender (P < 0.001) and Mefenamic acid group (P < 0.001). Conclusion: Lavender and Mefenamic acid can effectively relieve the menstrual pain severity and duration. Regarding to the side effects of Mefenamic acid, lavender in the form of aromatherapy can be an appropriate substitution.